Pengaruh Kecerdasan Emosional Pemimpin terhadap Kinerja dan Loyalitas Karyawan di PT Riau Andalan Pulp and Paper Bisnis Unit Riau Fiber - Marpaung, Rio; Krisna, Maria (Jurnal Aplikasi Manajemen, 2012)
Becoming a leader is never an easy task. A leader is requied to take charge of his organizationand help it reach it's goals. There are many ways that a leader could use to improve his subordinates'perfomance and to get their loyalties. One of the characteristics that a leader must have is a high Emotionalintelligence, comprised of Emotional Awareness, Self-management, Motivation, Empathy, and Social skill.This Emotional Intellegence could help a leader be more productive and more successful towards his goalsand help his subordinates to be more productive as well. This research is an analytical survey to analyze theinfuence of Emotional Intellegence of leadertowards the job perfomance and loyalty of employees in PT.Riau Andalan Pulp and Paper, Riaufiber Business Unit. The population of this research is 141 employeesfromvarious levels, sexes, positions, ages, educational backgrounds and length of services. Questionnaire isused as a method to gain the data for this research and SPSS 19 is used to analyze the data. The conclusionof this research shows that the Emotional Intellegence of a leader do infuence the Job Perfomance (a=0,044),the Emotional Intellegence of a leader do influence the Loyalty (a=0,356), and the Job Perfomance influencesthe Loyalty (a=0,288). It is recommende that a leader should improve his leadership by improving hisEmotional Intellegence so that the Job Perfomance and Loyalty Of his subordinates could also be improved.